Frequency of Premenstrual Syndrome and Its Association with Quality of Life among University Students - Irshad, Asmah; Mehmood, Sajid; Rabiya Noor; Mumtaz, Sara; Saleem, Maham; Talha Laique (Pakistan Journal of Medical & Health Sciences, 2022)
About 70% of the females are affected from premenstrual syndrome (PMS) and 45% are those who are severely affected that the symptoms affecting their daily life routine. Objectives: To find the frequency of premenstrual syndrome among university students and the association of premenstrual syndrome with quality of life. Study Design: Cross-sectional study. Methodology: Data of 500 university students (UHS, AIMC, SIMS and FAST NU) was gathered through two questionnaires, one for diagnosis of premenstrual syndrome (PMS) and other was SF-36 Quality of Life Questionnaire to check association of premenstrual syndrome (PMS) with quality of life. Statistical analysis: Data was analyzed using SPSS version 20. Percentages and graphs were given for the qualitative variables while Mean± SD were given for quantitative variables. Results: 339 students were diagnosed with premenstrual syndrome (PMS) and then quality of life was assessed using SF-36 to find the association with premenstrual syndrome. 67.8% of the females in a given sample having premenstrual syndrome. Conclusion: It was concluded that prevalence of premenstrual syndrome was high. Quality of life was majorly disturbed in several domains which emphasized that the premenstrual syndrome was directly associated with disturbed quality of life.